A carrier-free composite flame retardant masterbatch and its preparation method and application

By preparing the carrier-free composite flame retardant masterbatch, the flame retardant masterbatch in the prior art is solved by using the modification of ultrafine magnesium hydroxide, antimony trioxide and silane coupling agent, combined with microcrystalline wax and additives. The problems of limited addition ratio and poor versatility have achieved efficient flame retardant and low-cost carrier-free composite flame retardant masterbatches, significantly improving flame retardant performance and versatility, while maintaining physical and mechanical properties.

CN116554580BActive Publication Date: 2024-12-20JIANGXI GUANGYUAN CHEM +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310586872.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-23
Publication Date
2024-12-20
Estimated Expiration
2043-05-23

AI Technical Summary

Technical Problem

Due to the existence of carrier resin, the addition ratio of existing plastic flame retardant masterbatches is limited, the versatility is poor, and the physical and mechanical properties of the products have a great impact. No flame retardant can meet the flame retardant performance and thermal stability at the same time. Processing dispersion and cost requirements.

Method used

Using carrier-free composite flame retardant masterbatch, it is prepared by mixing ultrafine magnesium hydroxide, antimony trioxide and silane coupling agent, combined with microcrystalline wax and additives, and is prepared by extrusion granulation to form a modified composite Flame retardant improves the addition ratio and dispersion of flame retardant in masterbatch, and enhances flame retardant performance and versatility.

Benefits of technology

It realizes a carrier-free composite flame retardant masterbatch with excellent flame retardant performance, reduced cost and good physical and mechanical properties in plastic products. It can effectively retardant in PVC materials, reduce smoke and toxic gas generation, and improve flame retardant. Smoke suppression characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116554580B_ABST
    Figure CN116554580B_ABST
Patent Text Reader

Abstract

The present invention provides a carrier-free composite flame retardant masterbatch and a preparation method and application thereof, belonging to the technical field of flame retardant materials. When the carrier-free composite flame retardant masterbatch prepared by the present invention is applied to PVC (SG-5), antimony trioxide melts at the initial stage of combustion, forms a protective film on the surface of the material to isolate the air, and reduces the combustion temperature through an internal endothermic reaction; magnesium hydroxide will also decompose to absorb heat, and will also produce a lot of moisture and carbonized layers to prevent the flame from further contacting oxygen, so that the temperature of the PVC material will no longer continue to rise, extinguish the combustion, and block the continued occurrence of fire; antimony trioxide will gasify in the later stage, and the moisture produced by the decomposition of magnesium hydroxide will dilute the oxygen concentration in the air, thereby playing a flame retardant role. In addition, magnesium hydroxide greatly reduces the amount of smoke and the generation of toxic gases when PVC burns, and has excellent flame retardant and smoke suppression properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant materials, and in particular to a carrier-free composite flame retardant masterbatch and a preparation method and application thereof. Background Art

[0002] Plastic masterbatch is a concentrate made by attaching an extraordinary amount of plastic additives to the resin. There are many types of masterbatches, and filler masterbatch is one of them. The main component of filler masterbatch is filler, which accounts for more than 80%, and the carrier resin generally contains 10-20%. The benefits of using masterbatch in the plastic industry are: it is more convenient to mix raw materials, the mixing quality is uniform, the production efficiency is improved, the dust is reduced, the wear of equipment is reduced, and the shelf life of raw material storage is extended. However, due to the presence of carrier resin, the addition ratio of masterbatch cannot be further increased, or the masterbatch cannot be universal, and some physical and mechanical properties of plastic products are reduced to a certain extent.

[0003] In addition to having good flame retardant properties, flame retardants used to make plastic flame retardant masterbatches should also have good thermal stability, good processing dispersibility, little impact on the mechanical properties of the product, and long-lasting flame retardant properties. At the same time, abundant raw material sources and low prices are also considered. Obviously, no flame retardant can meet the above requirements at the same time, so researchers usually choose two or more flame retardants to match each other, which can produce a synergistic effect and achieve the effect of reducing costs.

[0004] Carrier-free filler masterbatch refers to a polymer material with a closed-cell structure that is made by mixing inorganic or organic fillers with a certain amount of foaming agent, flame retardant and other components. Carrier-free composite flame retardant masterbatch can achieve excellent flame retardant effect while optimizing costs to the greatest extent by matching two flame retardants in a certain proportion. Carrier-free masterbatch can not only increase the proportion of composite flame retardant added to the masterbatch, but also has strong versatility and satisfactory improvement in dispersibility in plastic products. More importantly, the physical and mechanical properties of plastic products are reduced very little, ensuring the physical and mechanical properties of the product.

[0005] In summary, it is still of great significance to study new carrier-free composite flame retardant masterbatches. Summary of the invention

[0006] The purpose of the present invention is to provide a carrier-free composite flame retardant masterbatch and a preparation method and application thereof. The prepared carrier-free composite flame retardant masterbatch has excellent flame retardant properties, can increase the addition ratio of the composite flame retardant in the masterbatch, has strong versatility, good dispersibility and compatibility in plastic products, and the physical and mechanical properties of the plastic products are rarely reduced.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a carrier-free composite flame retardant masterbatch, comprising the following steps:

[0009] Ultrafine magnesium hydroxide, antimony trioxide and a silane coupling agent are mixed and modified to obtain a modified composite flame retardant; the ultrafine magnesium hydroxide has a D 97 =4.5~4.8μm;

[0010] The modified composite flame retardant, microcrystalline wax and auxiliary agent are mixed, the obtained mixture is extruded and granulated, and then granulated to obtain a carrier-free composite flame retardant masterbatch.

[0011] Preferably, the method for preparing the ultrafine magnesium hydroxide comprises the following steps:

[0012] After crushing the brucite ore, the obtained ore is mixed with a grinding aid and a grinding medium, and wet-grinded to obtain a ball-milled material;

[0013] The ball-milled material is subjected to cyclone airflow classification to obtain ultrafine magnesium hydroxide.

[0014] Preferably, the grinding aid comprises alcohol, a carbonyl-containing polymer and a coupling agent; the mass ratio of the alcohol, the carbonyl-containing polymer and the coupling agent is (5-6):(1-2):(1-2); the mass of the grinding aid is 7-10‰ of the total mass of the ore.

[0015] Preferably, the carbonyl-containing polymer is one or more of polymaleic anhydride, sodium polyacrylate and polyacrylamide; the alcohol is one or more of ethylene glycol, diethylene glycol and triethanolamine; the coupling agent is one or more of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane.

[0016] Preferably, the mass ratio of the ultrafine magnesium hydroxide to antimony trioxide is 2-4:1; the mass of the silane coupling agent is 8-12‰ of the total mass of the ultrafine magnesium hydroxide and antimony trioxide.

[0017] Preferably, the modification temperature is 75-85° C. and the modification time is 2 hours.

[0018] Preferably, the mass of the microcrystalline wax is 0.7-1% of the mass of the modified composite flame retardant, and the mass of the auxiliary agent is 5-7% of the mass of the modified composite flame retardant; the auxiliary agent includes a coupling agent, polyethylene wax and zinc stearate; the mass of the coupling agent is 0.5-1.0% of the mass of the modified composite flame retardant, the mass of the polyethylene wax is 3-5% of the mass of the modified composite flame retardant, and the mass of the zinc stearate is 0.5-1.0% of the mass of the modified composite flame retardant.

[0019] Preferably, the extrusion granulation is carried out in a twin-screw extruder, the temperature range of each zone of the twin-screw extruder is independently 160-185° C., and the screw speed is 300-600 rpm; the speed of the pelletizer used for the pelletizing is 300-600 rpm.

[0020] The present invention provides a carrier-free composite flame retardant masterbatch prepared by the preparation method described in the above technical scheme.

[0021] The present invention provides application of the carrier-free composite flame retardant masterbatch described in the above technical solution in PVC material.

[0022] The present invention provides a method for preparing a carrier-free composite flame retardant masterbatch. The present invention adopts magnesium hydroxide and antimony trioxide as composite flame retardants, and adopts a silane coupling agent to modify the composite flame retardant. The hydrophilic group of the silane coupling agent has great affinity. The silane coupling agent and magnesium hydroxide and antimony trioxide are chemically bonded in a similar manner to chemical bonds. The lipophilic group of the silane coupling agent is oriented on the surface of the composite flame retardant to form a monomolecular film, which can produce an interface effect with a polymer matrix, thereby significantly improving the dispersibility and compatibility of the masterbatch in the polymer matrix. The modified composite flame retardant changes from hydrophilic to lipophilic, has good affinity to resinous organic matter, and thus improves various application properties of plastic products.

[0023] The ultrafine magnesium hydroxide used in the present invention has fineness, and when applied to polymers, the number of particles per unit area is large, the density is high, and thus the mechanical properties of the plastic products are less reduced.

[0024] The present invention adopts microcrystalline wax instead of resin as the masterbatch matrix, which can increase the addition ratio of the composite flame retardant in the masterbatch and has strong versatility.

[0025] When the carrier-free composite flame retardant masterbatch prepared by the present invention is applied to PVC (SG-5), antimony trioxide melts at the initial stage of combustion, forms a protective film on the surface of the material to isolate the air, and reduces the combustion temperature through internal endothermic reaction; magnesium hydroxide will also decompose and absorb heat, and will also produce a lot of moisture and carbonized layers to prevent the flame from further contacting with oxygen, so that the temperature of the PVC material will no longer continue to rise, extinguish the combustion, and block the continued occurrence of fire; antimony trioxide will gasify in the later stage, and dilute the oxygen concentration in the air with the moisture generated by the decomposition of magnesium hydroxide, thereby playing a flame retardant role. In addition, magnesium hydroxide greatly reduces the amount of smoke and the generation of toxic gases when PVC burns, and has excellent flame retardant and smoke suppression properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a flow chart for preparing a carrier-free composite flame retardant masterbatch. DETAILED DESCRIPTION

[0027] like Figure 1 As shown, the present invention provides a method for preparing a carrier-free composite flame retardant masterbatch, comprising the following steps:

[0028] Ultrafine magnesium hydroxide, antimony trioxide and a silane coupling agent are mixed and modified to obtain a modified composite flame retardant; the ultrafine magnesium hydroxide has a D 97 =4.5~4.8μm;

[0029] The modified composite flame retardant, microcrystalline wax and auxiliary agent are mixed, the obtained mixture is extruded and granulated, and then granulated to obtain a carrier-free composite flame retardant masterbatch.

[0030] In the present invention, unless otherwise specified, the required reagents, materials or equipment are all commercially available products well known to those skilled in the art.

[0031] The invention mixes ultrafine magnesium hydroxide, antimony trioxide and a silane coupling agent, performs modification, and obtains a modified composite flame retardant.

[0032] In the present invention, the method for preparing ultrafine magnesium hydroxide preferably comprises the following steps:

[0033] After crushing the brucite ore, the obtained ore is mixed with a grinding aid and a grinding medium, and wet-grinded to obtain a ball-milled material;

[0034] The ball-milled material is subjected to cyclone airflow classification to obtain ultrafine magnesium hydroxide.

[0035] The present invention has no special limitation on the source and composition of the brucite ore, and the brucite ore can be obtained in a manner well known in the art.

[0036] In the present invention, the brucite ore is preferably washed and then crushed once and twice in sequence to obtain ore; the present invention has no particular limitation on the washing, primary crushing and secondary crushing, and the ore with the required particle size can be obtained according to the process well known in the art.

[0037] In the present invention, the particle size of the ore is preferably 20 to 40 mm.

[0038] In the present invention, the ore is preferably conveyed to a ball mill, and then a grinding aid is pumped into the ball mill at a rate of 14 to 20 kg / h, more preferably 16 to 18 kg / h.

[0039] In the present invention, the grinding aid preferably includes alcohol, carbonyl-containing polymer and coupling agent; the mass ratio of the alcohol, carbonyl-containing polymer and coupling agent is preferably (5-6):(1-2):(1-2), more preferably 6:2:2; the grinding aid is more preferably a mixture of ethylene glycol, polyacrylamide and γ-aminopropyltriethoxysilane in a mass ratio of 6:2:2. In the present invention, the mass of the grinding aid is preferably 7-10‰ of the total mass of the ore, more preferably 8-9‰. The grinding aid used in the present invention can accelerate the grinding speed and prevent agglomeration.

[0040] In the present invention, the carbonyl-containing polymer is preferably one or more of polymaleic anhydride, sodium polyacrylate and polyacrylamide; the alcohol is preferably one or more of ethylene glycol, diethylene glycol and triethanolamine; the coupling agent is preferably one or more of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane; when the carbonyl-containing polymer, alcohol or coupling agent is two or more of the above, the present invention has no special limitation on the ratio of different types of compounds, which can be adjusted according to actual needs.

[0041] In the present invention, the grinding media is preferably 22 ton weight zirconium beads.

[0042] In the present invention, the rotation speed of the ball mill used for the wet ball milling is preferably 3600 r / min, and the ball milling time is preferably 60 min.

[0043] The present invention has no special limitation on the cyclone airflow classification, and ultrafine magnesium hydroxide with a desired particle size can be obtained according to a process well known in the art.

[0044] In the present invention, the D of the ultrafine magnesium hydroxide 97 =4.5~4.8μm.

[0045] The magnesium hydroxide produced by wet ball milling in the present invention has secondary classification and high powder absorption content. The zirconium beads are used as grinding media, which can effectively reduce the iron impurities brought by grinding media such as steel balls and steel segments, and the purity of the product is higher. Due to the use of grinding aids, agglomeration can be prevented to a certain extent during the ultra-fine process. Compared with similar magnesium hydroxides available on the market, the ultra-fine magnesium hydroxide prepared by the present invention has a higher cost performance while achieving the same flame retardant effect.

[0046] In the present invention, the silane coupling agent is preferably γ-aminopropyltriethoxysilane (KH550); the mass ratio of the ultrafine magnesium hydroxide to antimony trioxide is preferably 2-4:1, more preferably 3:1; the mass of the silane coupling agent is preferably 8-12‰ of the total mass of the ultrafine magnesium hydroxide and antimony trioxide, more preferably 10‰.

[0047] In the present invention, the process of mixing the ultrafine magnesium hydroxide, antimony trioxide and silane coupling agent is preferably to stir the ultrafine magnesium hydroxide and antimony trioxide in a high-speed stirrer, and add the silane coupling agent to the resulting mixture. The present invention has no particular limitation on the speed of the high-speed stirrer, and a high-speed stirrer well known in the art can be used for stirring.

[0048] In the present invention, the modification temperature is preferably 75-85°C, more preferably 80°C, and the modification time is preferably 2 hours; the modification is preferably carried out under stirring conditions, and the present invention has no special limitation on the stirring rate, and the modification can be carried out according to the process well known in the art. In the modification process, the silane coupling agent is coated on the two flame retardants, ultrafine magnesium hydroxide and antimony trioxide.

[0049] After obtaining the modified composite flame retardant, the present invention mixes the modified composite flame retardant, microcrystalline wax and an auxiliary agent, extrudes and granulates the obtained mixture, and then cuts the mixture into pellets to obtain a carrier-free composite flame retardant masterbatch.

[0050] In the present invention, the mass of the microcrystalline wax is preferably 0.7-1% of the mass of the modified composite flame retardant, and more preferably 0.8-0.9%. The present invention utilizes microcrystalline wax as a carrier of the masterbatch. Microcrystalline wax is generally composed of relatively fine needle-shaped or granular crystals. Microcrystalline wax has low hardness and good flexibility. It is easy to deform after being subjected to force and is not easy to break. The main components of microcrystalline wax are cycloalkanes and aromatic hydrocarbons with large molecular weight and long carbon chains, so it has a certain plasticity. The present invention utilizes the plasticity of microcrystalline wax to exert the same load-bearing capacity as ordinary resin, and uses microcrystalline wax as a matrix for masterbatch.

[0051] In the present invention, the mass of the auxiliary agent is preferably 5-7% of the mass of the modified composite flame retardant, and more preferably 5.5-6.5%; the auxiliary agent preferably includes a coupling agent, polyethylene wax and zinc stearate; the coupling agent is preferably γ-aminopropyltriethoxysilane (KH550); the mass of the coupling agent is preferably 0.5-1.0% of the mass of the modified composite flame retardant, and more preferably 0.6-0.8%, the mass of the polyethylene wax is preferably 3-5% of the mass of the modified composite flame retardant, and more preferably 3.5-4%, the mass of the zinc stearate is preferably 0.5-1.0% of the mass of the modified composite flame retardant, and more preferably 0.6-0.7%; in the present invention, the coupling agent is used as a surface modifier, and when it is used for inorganic fillers to fill plastics, its dispersibility and adhesion can be improved; polyethylene wax is used as a lubricant, and zinc stearate is used as a lubricant and a release agent.

[0052] The present invention has no special limitation on the process of mixing the modified composite flame retardant, microcrystalline wax and additives, and the materials can be mixed evenly according to a process well known in the art.

[0053] In the present invention, the extrusion granulation is preferably carried out in a twin-screw extruder, and the temperature range of each zone of the twin-screw extruder is preferably 160-185°C, and the screw speed is preferably 300-600rpm, more preferably 350rpm. The present invention has no special limitation on the specific distribution values ​​of the temperature in each zone of the twin-screw extruder, and can be adjusted within the above range according to actual needs.

[0054] In the present invention, the speed of the pelletizer used for pelletizing is preferably 300 to 600 rpm, more preferably 400 to 500 rpm.

[0055] After the pelletizing is completed, the present invention preferably dries the obtained material to obtain a carrier-free composite flame retardant masterbatch.

[0056] In the present invention, the particle size of the carrier-free composite flame retardant masterbatch is preferably 3 to 4 mm.

[0057] The present invention provides a carrier-free composite flame retardant masterbatch prepared by the preparation method described in the above technical scheme.

[0058] The present invention provides the application of the carrier-free composite flame retardant masterbatch in the above technical solution in PVC materials. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.

[0059] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0060] Example 1

[0061] The brucite ore is washed, broken once, and broken twice to obtain an ore with a particle size of 20 to 40 mm, and the ore is transported to a ball mill. At the same time, a grinding aid (ethylene glycol: polyacrylamide: γ-aminopropyltriethoxysilane = 6:2:2, mass ratio) is pumped into the ball mill at a speed of 14 kg / h, and the mass of the grinding aid is 7‰ of the total mass of the ore. The grinding medium in the grinder is 22 tons of zirconium beads. Wet ball milling is performed at a speed of 3600 r / min for 60 minutes to obtain a ball-milled material;

[0062] The ball-milled material is subjected to cyclone airflow classification to obtain ultrafine magnesium hydroxide powder, D 97 =4.5~4.8μm;

[0063] The ultrafine magnesium hydroxide powder and antimony trioxide are fully stirred and mixed in a high-speed mixer at a mass ratio of 4:1, and a silane coupling agent KH550 accounting for 8‰ of the mass of the mixture is added to the obtained mixture, and the reaction is continued at 75° C. for 2 hours to obtain a modified composite flame retardant;

[0064] The modified composite flame retardant is mixed with microcrystalline wax and additives at high speed, wherein the mass of the microcrystalline wax is 1% of the mass of the modified composite flame retardant, the total mass of the additives is 7% of the mass of the modified composite flame retardant, and the additives include 1% of a coupling agent (KH550), 5% of polyethylene wax, and 1% of zinc stearate; the obtained mixture is extruded and granulated through a twin-screw extruder, and the temperature distribution of each zone of the twin-screw extruder is 160°C, 165°C, 170°C, 175°C, 180°C, 180°C, 185°C, 180°C, 180°C, 175°C, 170°C, 170°C; the screw speed is 350rpm; the obtained screw extrusion product is pelletized, the pelletizer speed is 500rpm, and the pelletized product is dried to obtain a carrier-free composite flame retardant masterbatch with a particle size of 3-4mm.

[0065] Example 2

[0066] The brucite ore is washed, broken once, and broken twice to obtain an ore with a particle size of 20 to 40 mm, and the ore is transported to a ball mill. At the same time, a grinding aid (ethylene glycol: polyacrylamide: γ-aminopropyltriethoxysilane = 6:2:2, mass ratio) is pumped into the ball mill at a speed of 14 kg / h, and the mass of the grinding aid is 7‰ of the total mass of the ore. The grinding medium in the grinder is 22 tons of zirconium beads. Wet ball milling is performed at a speed of 3600 r / min for 60 minutes to obtain a ball-milled material;

[0067] The ball-milled material is subjected to cyclone airflow classification to obtain ultrafine magnesium hydroxide powder, D 97 =4.5~4.8μm;

[0068] The ultrafine magnesium hydroxide powder and antimony trioxide are fully stirred and mixed in a high-speed mixer at a mass ratio of 4:1, and a silane coupling agent KH550 accounting for 8‰ of the mass of the mixture is added to the obtained mixture, and the reaction is continued at 80° C. for 2 hours to obtain a modified composite flame retardant;

[0069] The modified composite flame retardant is mixed with microcrystalline wax and additives at high speed, wherein the mass of the microcrystalline wax is 1% of the mass of the modified composite flame retardant, the total mass of the additives is 7% of the mass of the modified composite flame retardant, and the additives include 1% of a coupling agent (KH550), 5% of polyethylene wax, and 1% of zinc stearate; the obtained mixture is extruded and granulated through a twin-screw extruder, and the temperature distribution of each zone of the twin-screw extruder is 160°C, 165°C, 170°C, 175°C, 180°C, 180°C, 185°C, 180°C, 180°C, 175°C, 170°C, 170°C; the screw speed is 350rpm; the obtained screw extrusion product is pelletized, the pelletizer speed is 500rpm, and the pelletized product is dried to obtain a carrier-free composite flame retardant masterbatch with a particle size of 3-4mm.

[0070] Example 3

[0071] The brucite ore is washed, broken once, and broken twice to obtain an ore with a particle size of 20 to 40 mm, and the ore is transported to a ball mill. At the same time, a grinding aid (ethylene glycol: polyacrylamide: γ-aminopropyltriethoxysilane = 6:2:2, mass ratio) is pumped into the ball mill at a speed of 14 kg / h, and the mass of the grinding aid is 7‰ of the total mass of the ore. The grinding medium in the grinder is 22 tons of zirconium beads. Wet ball milling is performed at a speed of 3600 r / min for 60 minutes to obtain a ball-milled material;

[0072] The ball-milled material is subjected to cyclone airflow classification to obtain ultrafine magnesium hydroxide powder, D 97 =4.5~4.8μm;

[0073] The ultrafine magnesium hydroxide powder and antimony trioxide are fully stirred and mixed in a high-speed mixer at a mass ratio of 3:1, and 10‰ of the mass of the mixed material is added to the obtained mixture. The mixture is reacted for 2 hours at 80°C to obtain a modified composite flame retardant;

[0074] The modified composite flame retardant is mixed with microcrystalline wax and additives at high speed, wherein the mass of the microcrystalline wax is 1% of the mass of the modified composite flame retardant, the total mass of the additives is 7% of the mass of the modified composite flame retardant, and the additives include 1% of a coupling agent (KH550), 5% of polyethylene wax, and 1% of zinc stearate; the obtained mixture is extruded and granulated through a twin-screw extruder, and the temperature distribution of each zone of the twin-screw extruder is 160°C, 165°C, 170°C, 175°C, 180°C, 180°C, 185°C, 180°C, 180°C, 175°C, 170°C, 170°C; the screw speed is 350rpm; the obtained screw extrusion product is pelletized, the pelletizer speed is 500rpm, and the pelletized product is dried to obtain a carrier-free composite flame retardant masterbatch with a particle size of 3-4mm.

[0075] Example 4

[0076] The brucite ore is washed, broken once, and broken twice to obtain an ore with a particle size of 20 to 40 mm, and the ore is transported to a ball mill. At the same time, a grinding aid (ethylene glycol: polyacrylamide: γ-aminopropyltriethoxysilane = 6:2:2, mass ratio) is pumped into the ball mill at a speed of 14 kg / h, and the mass of the grinding aid is 7‰ of the total mass of the ore. The grinding medium in the grinder is 22 tons of zirconium beads. Wet ball milling is performed at a speed of 3600 r / min for 60 minutes to obtain a ball-milled material;

[0077] The ball-milled material is subjected to cyclone airflow classification to obtain ultrafine magnesium hydroxide powder, D 97 =4.5~4.8μm;

[0078] The ultrafine magnesium hydroxide powder and antimony trioxide are fully stirred and mixed in a high-speed mixer at a mass ratio of 2:1, and 12‰ of the mass of the mixed material is added to the obtained mixture. The mixture is reacted for 2 hours at 80°C to obtain a modified composite flame retardant;

[0079] The modified composite flame retardant is mixed with microcrystalline wax and additives at high speed, wherein the mass of the microcrystalline wax is 1% of the mass of the modified composite flame retardant, the total mass of the additives is 7% of the mass of the modified composite flame retardant, and the additives include 1% of a coupling agent (KH550), 5% of polyethylene wax, and 1% of zinc stearate; the obtained mixture is extruded and granulated through a twin-screw extruder, and the temperature distribution of each zone of the twin-screw extruder is 160°C, 165°C, 170°C, 175°C, 180°C, 180°C, 185°C, 180°C, 180°C, 175°C, 170°C, 170°C; the screw speed is 350rpm; the obtained screw extrusion product is pelletized, the pelletizer speed is 500rpm, and the pelletized product is dried to obtain a carrier-free composite flame retardant masterbatch with a particle size of 3-4mm.

[0080] Example 5

[0081] The brucite ore is washed, broken once, and broken twice to obtain an ore with a particle size of 20 to 40 mm, and the ore is transported to a ball mill. At the same time, a grinding aid (ethylene glycol: polyacrylamide: γ-aminopropyltriethoxysilane = 6:2:2, mass ratio) is pumped into the ball mill at a speed of 14 kg / h, and the mass of the grinding aid is 7‰ of the total mass of the ore. The grinding medium in the grinder is 22 tons of zirconium beads. Wet ball milling is performed at a speed of 3600 r / min for 60 minutes to obtain a ball-milled material;

[0082] The ball-milled material is subjected to cyclone airflow classification to obtain ultrafine magnesium hydroxide powder, D 97 =4.5~4.8μm;

[0083] The ultrafine magnesium hydroxide powder and antimony trioxide are fully stirred and mixed in a high-speed mixer at a mass ratio of 2:1, and 12‰ of the mass of the mixed material is added to the obtained mixture. The mixture is reacted for 2 hours at 80°C to obtain a modified composite flame retardant;

[0084] The modified composite flame retardant is mixed with microcrystalline wax and additives at high speed, wherein the mass of the microcrystalline wax is 0.8% of the mass of the modified composite flame retardant, the total mass of the additives is 5.5% of the mass of the modified composite flame retardant, and the additives include 0.8% of a coupling agent (KH550), 4% of polyethylene wax, and 0.7% of zinc stearate; the obtained mixture is extruded and granulated through a twin-screw extruder, and the temperature distribution of each zone of the twin-screw extruder is 160°C, 165°C, 170°C, 175°C, 180°C, 180°C, 185°C, 180°C, 180°C, 175°C, 170°C, and 170°C; the screw speed is 350rpm; the obtained screw extrusion product is pelletized, the pelletizer speed is 500rpm, and the pelletized product is dried to obtain a carrier-free composite flame retardant masterbatch with a particle size of 3-4mm.

[0085] Comparative Example 1

[0086] The ultrafine magnesium hydroxide prepared in Example 1 was used as Comparative Example 1.

[0087] Comparative Example 2

[0088] Antimony trioxide was used as Comparative Example 2.

[0089] Performance Testing

[0090] The products of comparative examples 1 to 2 and different masterbatches of examples 1 to 5 were used in PVC (SG-5) respectively, and the masterbatch addition amount was 10wt%. After mixing PVC with the masterbatch, the PVC was smelted with an open mill, the smelting temperature was 170°C, the smelting time was 6min, and then the tablet was pressed with a tablet press at 170°C for 3min, the pressure was 15MPa, pressed into a fixed thickness, and cut into standard strips with a pneumatic cutting machine for testing. Among them, the tensile strength was tested according to the standard GB / T1040-2018, the specific gravity was tested according to the standard GBT1033.1-2008 method, the smoke density was tested according to the standard GB / T8627-2007 using a building material smoke density tester, and the oxygen index was tested according to the standard GB / T2406.2-2009. The test results are shown in Table 1.

[0091] Table 1 Performance test results of different masterbatches applied to PVC in Comparative Examples 1-2 and Examples 1-5

[0092]

[0093] It can be seen from Table 1 that compared with pure magnesium hydroxide, the carrier-free composite flame retardant masterbatch prepared by the present invention has a higher oxygen index, and compared with pure antimony trioxide, the carrier-free composite flame retardant masterbatch prepared by the present invention has a smaller smoke density, indicating that the flame retardancy of the carrier-free composite flame retardant masterbatch is better; at the same time, the mechanical properties of the PVC product are slightly reduced.

[0094] As can be seen from the above embodiments, the present invention provides a method for preparing a carrier-free composite flame retardant masterbatch. When the carrier-free composite flame retardant masterbatch prepared by the present invention is applied to PVC (SG-5), antimony trioxide melts at the initial stage of combustion, and a protective film is formed on the surface of the material to isolate the air, and the combustion temperature is reduced by an internal endothermic reaction; magnesium hydroxide will also decompose and absorb heat, and will also produce a lot of moisture and carbonized layers to prevent the flame from further contacting oxygen, so that the temperature of the PVC material will no longer continue to rise, extinguish the combustion, and block the continued occurrence of fire; antimony trioxide will gasify in the later stage, and the moisture generated by the decomposition of magnesium hydroxide will dilute the oxygen concentration in the air, thereby playing a flame retardant role. In addition, magnesium hydroxide greatly reduces the amount of smoke and the generation of toxic gases when PVC burns, and has excellent flame retardant and smoke suppression properties.

[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a carrier-free composite flame retardant masterbatch, characterized in that: The following steps are involved: Ultrafine magnesium hydroxide, antimony trioxide and a silane coupling agent are mixed and modified to obtain a modified composite flame retardant; The ultrafine magnesium hydroxide D 97 =4.5~4.8μm; The modified composite flame retardant, microcrystalline wax and additives are mixed, the obtained mixture is extruded and granulated, and then pelletized to obtain a carrier-free composite flame retardant masterbatch; The mass of the silane coupling agent is 8-12‰ of the total mass of the ultrafine magnesium hydroxide and antimony trioxide; The mass of the microcrystalline wax is 0.7-1% of the mass of the modified composite flame retardant; The mass ratio of the ultrafine magnesium hydroxide to antimony trioxide is 2-4:

1.

2. The preparation method according to claim 1, characterized in that: The preparation method of the ultrafine magnesium hydroxide comprises the following steps: After crushing the brucite ore, the obtained ore is mixed with a grinding aid and a grinding medium, and wet-grinded to obtain a ball-milled material; The ball-milled material is subjected to cyclone airflow classification to obtain ultrafine magnesium hydroxide.

3. The preparation method according to claim 2, characterized in that: The grinding aid comprises alcohol, a carbonyl-containing polymer and a coupling agent; the mass ratio of the alcohol, the carbonyl-containing polymer and the coupling agent is (5-6):(1-2):(1-2); the mass of the grinding aid is 7-10‰ of the total mass of the ore.

4. The preparation method according to claim 3, characterized in that: The carbonyl-containing polymer is one or more of polymaleic anhydride, sodium polyacrylate and polyacrylamide; the alcohol is one or more of ethylene glycol, diethylene glycol and triethanolamine; the coupling agent is one or more of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane and vinyltri(β-methoxyethoxy)silane.

5. The preparation method according to claim 1, characterized in that: The modification temperature is 75-85°C and the modification time is 2h.

6. The preparation method according to claim 1, characterized in that: The mass of the auxiliary agent is 5-7% of the mass of the modified composite flame retardant; the auxiliary agent includes a coupling agent, polyethylene wax and zinc stearate; the mass of the coupling agent is 0.5-1.0% of the mass of the modified composite flame retardant, the mass of the polyethylene wax is 3-5% of the mass of the modified composite flame retardant, and the mass of the zinc stearate is 0.5-1.0% of the mass of the modified composite flame retardant.

7. The preparation method according to claim 1, characterized in that: The extrusion granulation is carried out in a twin-screw extruder, the temperature range of each zone of the twin-screw extruder is independently 160-185° C., and the screw speed is 300-600 rpm; the speed of the pelletizer used for pelletizing is 300-600 rpm.

8. The carrier-free composite flame retardant masterbatch prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the carrier-free composite flame retardant masterbatch according to claim 8 in PVC materials.